Effect of organic manures and bio-fertilisers on growth and quality of kharif onion (Allium cepa L.) in semi-arid region (Indian Journal of Arid Horticulture, 2016)
Onion (Allium cepa L.) is a bulbous biennial herb of the family Alliaceae. Commonly called the "Queen of the kitchen," it is used throughout the year in salads, condiments, and cooking with other vegetables. The pungency of onion is due to the sulfur compound "allyl propyl disulfide" in the volatile oil, and the outer yellow skin color is due to the presence of "quercetin" (Nadkarni, 1954). Onion bulbs are rich in minerals such as phosphorus (50 mg/100 g), iron (0.7 mg/100 g), calcium (18 mg/100 g), carbohydrates (11.0 g/100 g), protein (1.2 g/100 g), vitamin C (11 mg/100 g), fibers (0.6 g/100 g), and nicotinic acid (0.4 mg/100 g) (Aykroyd, 1963). The productivity of onion in India is relatively low (16 t ha-1) compared to other countries, indicating significant potential for increasing production through fertilizers, particularly organic manures and bio-fertilizers, in light-textured soil. Producing onions in the kharif season is crucial for ensuring a continuous supply throughout the year. Organic manures stimulate the production of polysaccharides and other compounds that improve soil aggregation, structure, tilth, aeration, and moisture movement and retention (Bose et al., 2001). Bio-fertilizer inoculation with Azospirillum and phosphorus-solubilizing bacteria (PSB) helps plants achieve better vegetative growth and increases yield by 10-30 percent (Mohandas, 1999; Tilak and Annapurna, 1993). This investigation was conducted to study the effect of organic manures and bio-fertilizers on kharif onion in a semi-arid region.
Keywords: phosphorus-solubilizing; organic; bio-fertilizers; kharif onion